Mutational Spectrum of LDLR and PCSK9 Genes Identified in Iranian Patients With Premature Coronary Artery Disease and Familial Hypercholesterolemia - Moradi, Arman; Maleki, Majid; Ghaemmaghami, Zahra; Khajali, Zahra; Noohi, Feridoun; Moghadam, Maryam Hosseini; Kalyinia, Samira; Mowla, Seyed Javad; Seidah, Nabil G.; Malakootian, Mahshid (Frontiers in Genetics, 2021)
Familial hypercholesterolemia (FH) is a common, yet underdiagnosed, genetic disorder characterized by lifelong elevated low-density lipoprotein cholesterol levels, which can increase the risk of early-onset coronary artery disease (CAD). In the present study, we screened the nucleotide variations of the LDLR and PCSK9 genes, as well as a part of the APOB gene, in Iranian patients with FH and premature CAD to find the genetic cause of the disorder. Fifteen unrelated individuals with a clinical diagnosis of FH and premature CAD were recruited. Direct DNA sequencing was applied to screen the whole coding exons and exon-intron boundaries of the LDLR and PCSK9 genes and the main parts of their introns, together with exon 26 of the APOB gene. The pathogenicity of the identified mutations was investigated via either segregation analyses in the family or in silico predictive software. Six different point mutations (p.Cys148Tyr, p.Cys216Tyr, p.Cys302Trp, p.Cys338Trp, p.Leu479Gln, and p.G593Afs*72) in LDLR and a double mutation (p.Asp172His and p.Ala53Val) in both LDLR and PCSK9 genes were identified in 7 families with clinically diagnosed FH (43%), while no pathogenic mutations were found in 8 families with clinically diagnosed FH. This study is the first to identify 1 pathogenic mutation in the LDLR gene (c.1014C>G [p.Cys338Trp]) and to co-segregate it from the affected individual in the family. No mutations were found in the APOB gene, whereas several silent mutations/polymorphisms were identified in the LDLR and PCSK9 genes. Genetic testing and reports on nucleotide alterations in the Iranian population are still limited. Our findings not only further confirm the significant role of FH in the incidence of premature CAD but also enlarge the spectrum of LDLR and PCSK9 variations and exhibit the heterogeneity of FH in Iranians. In patients with no mutation in the examined genes, the disease could be begotten either by a polygenic cause or by gene defects occurring in other related genes and regions not targeted in this study.